2015
DOI: 10.1128/aem.00722-15
|View full text |Cite
|
Sign up to set email alerts
|

Rich Medium Composition Affects Escherichia coli Survival, Glycation, and Mutation Frequency during Long-Term Batch Culture

Abstract: Bacteria such as Escherichia coli are frequently grown to high density to produce biomolecules for study in the laboratory. To achieve this, cells can be incubated in extremely rich media that increase overall cell yield. In these various media, bacteria may have different metabolic profiles, leading to changes in the amounts of toxic metabolites produced. We have previously shown that stresses experienced during short-term growth can affect the survival of cells during the long-term stationary phase (LTSP). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 29 publications
0
47
0
Order By: Relevance
“…The full‐length GST‐EcdB protein was expressed in E. coli BL21(DE3) expression host by optimizing different expression conditions. A group of investigators revealed that protein expression or toxic protein expression can be improved by a subsequent alteration of IPTG concentration , temperature , using rich medium , induction at higher cell density , and induction on lawn cells in place of seed culture . We first tested IPTG (1 µM, 10 µM, 0.5 mM, and 1 mM) and lawn cells (10 µM IPTG)‐dependent induction at 37 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full‐length GST‐EcdB protein was expressed in E. coli BL21(DE3) expression host by optimizing different expression conditions. A group of investigators revealed that protein expression or toxic protein expression can be improved by a subsequent alteration of IPTG concentration , temperature , using rich medium , induction at higher cell density , and induction on lawn cells in place of seed culture . We first tested IPTG (1 µM, 10 µM, 0.5 mM, and 1 mM) and lawn cells (10 µM IPTG)‐dependent induction at 37 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The uninduced construct was treated as a negative control in the entire study. Based on previous reports, the full‐length (GST:EcdB) protein was expressed by optimizing three different parameters such as IPTG concentration, temperature, and growth medium . In spite of that, IPTG induction at lawn cells and higher cell density (1 OD) was also tested as investigated previously .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows the remaining 67 ~1% of cells to enter long-term stationary phase (LTSP), where they can use the 68 detritus of lysed cells as carbon and energy sources (10-12). The stresses of long-69 term stationary phase likely include high pH, high oxidative stress but low oxygen, 70 and a lack of readily metabolized nutrients, however none of these are 71 characterized completely (10, 13,14). We have previously shown that cells with 72 mutations that may help cope with these stresses are selected for during this 73 phase, and that as populations continue further into LTSP, there is turnover of 74 different mutant genotypes depending on the medium conditions at any given time 75 (7,9).…”
Section: Abstract 18mentioning
confidence: 99%
“…The expression of recombinant protein was influenced by severalfactors, IPTG concentration, Cell Optical Density, culture media composition (Studier 2005;Uhoraningonga et al, 2018), and temperature (Song et al, 2012).The low temperature cultivation (<28 o C) after induction with IPTG will formed protein in a soluble form and increase the yield of protein (Singh et al, 2015;Larentis et al, 2014;Carrio et al, 2005) While media composition will give high density cell culture or the induce the death of E. coli cells (Farrel and Finkel 2003). According to Kram and Finkel (2015), The effect of media compositionswill lead the oxidative stress, increasing of pH, the death of cells during log phase and changes in long-term survival patterns…”
Section: Introductionmentioning
confidence: 99%